Political philosophy in the Occultation according to Transcendental Theosophy - Murtaza Waez Jawadi (حکمت اسرا)
The present article seeks to explain the philosophy of governance during the Occultation [of the 12th Imam] by using a meta-political approach that is based on the Transcendental Theosophy [of Mulla Sadra]. Politics is a sub-branch of practical theosophy. The depth of a practical theosophy is indebted to the depth of the theoretical theosophy on which it is based. Thus Transcendental Theosophy as the most extensive and profound theosophical trend gives rise to a profound transcendental politics. Understanding the philosophy of a government is dependant on understanding the aims and objectives a government follows. In Transcendental Theosophy, politics is based on prophecy. The aim of prophecy is thus to promote an imperfect man to the level of perfection he or she deserves. To relate the philosophy of prophecy in such a way is different from and more profound than explaining it in accordance with the theory of ‘naturally civility’ or the law of ‘grace’, for according to transcendental analysis the philosophy includes not only societies but also individuals. Looking from this perspective, prophecy is not the requirement of human social needs but the requirement of Divine creatorship, guidance and divinity. It is in accordance with such an understanding that one can come to know that prophets are the vicegerents of God and after the prophets pass away it is the holy Imams, divine saints, and lastly jurists (in the age of Occultation) who replace them and assume their responsibilities. Thus according to Transcendental Theosophy, Islamic politics during the Occultation is a divine politics originating in prophecy. The present study attempts to outline this process and model of philosophical thinking in the course of 15 stages